Breeding ecology of red-tailed tropicbirds (Phaethon Rubricauda) on Nukutepipi, French Polynesia : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Zoology at Massey University, Palmerston North - Loussan, Aurélie (Massey University, 2025)
This thesis investigated the breeding ecology of red-tailed tropicbirds (Phaethon rubricauda) on the atoll Nukutepipi, French Polynesia, focusing on parental behaviours during the incubation and chick-rearing periods, and chick growth rates. From 1 March to 25 May 2024, the study monitored 55 eggs, 13 of which failed to hatch, resulting in a hatching success rate of 76.4%. Additionally, 24 hatched chicks present at the study’s outset were included. Parental behaviours during incubation were characterised by alternating shifts of incubation and foraging trips, which lasted an average of 10.4 days. Occasional desynchronisation between parents sometimes left eggs unattended, making them vulnerable to predation by strawberry hermit crabs (Coenobita perlatus). During the chick-rearing period, parental attendance decreased as chicks matured, dropping from 60% in the first 10 days to just 1% by day 80, with a slight increase approaching fledging. A bimodal foraging strategy was observed: long foraging trips for self-feeding (11.3 days) and short trips for chick provisioning (1.1 days). Meal sizes increased with chick age, starting at 18 g for younger chicks and reaching 86 g for older ones. The diet included fish from eight families, with Carangidae, Exocoetidae, and Balistidae being the most common. Chick growth varied significantly, with fledglings exhibiting adult-like head and tarsus-to-middle-toe lengths but shorter culmen, wing, and tail lengths. Body mass increased rapidly early in development, reaching an asymptotic mass of approximately 700 g before declining near fledging. Fasting periods, averaging 2.9 days, consisted of two phases. Of the 65 chicks monitored, only five fledged and 26 died, yielding a fledging success rate estimated to be between 7.7% and 60%. Starvation was the leading cause of chick mortality, accounting for 65.4% of deaths. This study provides valuable insights into the breeding ecology of red-tailed tropicbirds in the previously unstudied Nukutepipi colony.
Keywords: 310307 Population ecology